Biodegradation of lignocellulosicwastes by basidiomycetes fungi: Characterization of waste and study of fungal enzyme complex - Barreto, Andressa Ribas; Menezes, Cristiano Ragagnin de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Wide variety and quantity of organic waste are generated annually by human agribusiness activities. Waste materials are a negative factor in the economic evaluation of agricultural and forestry operations, causing adverse effects on the environment during its disposal. Thus, the need for further research in order to add value to products and by-products of agriculture, mainly by increasing the generation of these. The use of waste of Brazilian agribusiness and provide alternatives substrates for fermentation, also helps in environmental pollution problems. One of the possibilities in the degradation of lignocellulosic materials is the use of specific microorganisms that produce enzymes that hydrolyze cellulose, such as avicelase, carboxymethylcellulase and -glucosidase (cellulases) enzymes that act on the cellulosic portion, xylanases, mannanases, glucanases and galactanases (hemicellulases) that act on the hemicellulose portion and oxidative enzymes such as lignin peroxidase, manganese peroxidase and laccase, defined as phenoloxidases, acting on lignin. Thus, the aim of this review is to demonstrate the biodegradation potential of these agricultural waste by using lignocellulolytic enzymes produced by Basidiomycetes, which in the scientific literature, are seen as degrading natural these matrices.